Optimalkan Investasi: Pendekatan Hukum dalam Kerjasama Investor dan Perusahaan Kelapa Sawit - Djulya Eka Pusvita; Arini Asriyani (Jurnal Litigasi Amsir, 2023)
This research aims to find out and analyze the system for implementing investment cooperation agreements between investors and palm oil companies in Mamuju and to find out and analyze the legal protection of investors in implementing investment cooperation agreements between investors and palm oil companies in Mamuju. This legal research uses empirical juridical research. The research results show that the implementation of investment at PT. Surya Raya Lestari 2, which is a subsidiary of PT. Astra is regulated in the Introduction to Palm Oil Investment and Investment Cooperation Agreement stages. Customer self-monitoring is essential in ensuring smooth investment. Investor protection is embodied in futures exchange regulations. PT. Surya Raya Lestari 2 offers settlement options through internal civil proceedings or futures exchange institutions, as well as criminal proceedings through BAPPEBTI or law enforcement agencies, which confirms its legal commitment to guaranteeing investment security and sustainability.